Democratization and the Challenge of Electoral Violence in Nigeria: Reflections on 2003 Elections in Rivers State (Journal of Management and Social Sciences, 2017)
AbstractAs Nigeria returned to civil rule, expectations were high that democratic governance would facilitate the constructive resolution of conflicts threatening to tear the nation apart. Rather than aid the amelioration of conflict especially in the Niger Delta, the violence that has characterised democratic competition since 1999 has worsened the situation by introducing new dynamics to the region’s conflict trajectories. Using thequalitative research method where data is gathered through primary and secondary sources this study assesses the high stake politics and how actions of political stakeholders have worsened the conflict situation in the region. It discusses the commodification of violence, the militarisation of anti-state oil protests, and violence that ravaged the wider Niger Delta focusing on Rivers State. It argues that the spectre of violence in Rivers State and the region in general can be located within the context of the nature of Nigerian politics, in particular the struggle for the capture of the state and the control of oil rents. The Nigerian experience highlights the important position of contextual variables in the discussion of the conflict mitigating potential of democratic governance.